A Review of Employees’ Job Satisfaction and its Affect on their Retention - IRABOR, Ikechukwu Emmanuel; OKOLIE, Ugo Chuks (Annals of Spiru Haret University. Economic Series, 2019)
Learning about factors that influence staff retention and ways of improving it, can help organizations avoid the inconvenience of high attrition. The employee’s job satisfaction and retention are the main factors for the success and survival of any firm. No one can measure the level of satisfaction an individual get why he performs his work. But there are factors which directly or indirectly affect the satisfaction level of employees at workplace. Companies that constitute work environment that attract, motivate, and retain talented employees will be better positioned to succeed in today’s competitive business world that demands quality and cost-efficiency. The main challenges that organizations are facing today is not only managing its human resources but also satisfying and retaining them. Securing and retaining skilled workforce plays an important role for any organization, because the knowledge and skills of employees have become highly essential in gaining competitive advantage in today’s business environment. Thus, the objective of this paper was to: examine the factors which affect the job satisfaction of employees. Determine the affect of job satisfaction on employees’ retention and suggest recommendations on possible ways to improve employees’ retention. Also, the essential of having a retention strategy, which is based on a well enunciated human resource management system, was emphasized.